O013 Understanding the sexual appetites of men who have sex with men (MSM) taking part in a sexual risk reduction intervention after being prescribed post exposure prophylaxis for HIV after sexual exposure (PEPSE). (30th June 2016) - Parr, Alex; Llewellyn, Carrie
Abstract : Background/introduction: Risky sexual behaviours remain the drivers behind new HIV infections within MSM in the UK. Understanding reasons behind risk behaviour could inform HIV prevention strategies. Aim(s)/objectives: To document sexual appetite/libido among MSM taking PEPSE, and to examine the relations between libido and risk behaviours. Methods: Data were collected at enrolment, as part of an ongoing RCT evaluating a behavioural intervention to reduce HIV risk behaviour. Within this study, a 10-item measure of libido was included (possible range of scores 10–40). This assessed how much thoughts and feelings about sex were considered disruptive. Results: 171 MSM responded (mean age 34.5, SD 9.1, range 19–66 yrs). Mean ( SD ) libido score was 20.4 (7.7); median was 19 (range 30). Those with higher libido reported a higher number of sexual partners, both insertive ( rs = 0.298; p ≤ 0.001; n = 162) and receptive ( rs = 0.329; p ≤ 0.001; n = 164), and inconsistent condom use, both insertive ( rs = 0.185; p = 0.042; n = 121) and receptive ( rs = 0.227; p = 0.009; n = 132). Higher libido was associated with higher levels of loneliness ( rs = 0.401; p ≤ 0.001; n = 165); reduced self-efficacy ( rs = −0.230; p = 0.003; n = 165), action planning ( rs = −0.182; p = 0.019; n = 164), intentions ( rs = −0.163; p = 0.036; n = 165) and behavioural likelihood ( rs = −0.228; p = 0.003; n = 165) of performing safer sex strategies. Loneliness was related to inconsistent condom use, both insertive ( rs = 0.191; p = 0.021; n = 147) and receptive ( rs = 0.165; p = 0.036; n = 162), and a high number of sexual partners (receptive) ( rs = 0.164; p = 0.033; n = 171). Discussion/conclusion: Risky behaviours are related to stronger sexual appetites/libido and loneliness within this sample. The potential importance of libido and loneliness should be recognised within the context of future HIV prevention efforts.